Monopoli Perdagangan Pada Bisnis TikTok Shop yang Terjadi di Indonesia Perspektif Al-Taimiyah - wulandari, Devi (Program Studi Hukum Ekonomi Syariah, Institut Agama Islam Negeri Parepare, 2024)
Trade monopoly is a condition where one or several companies or individuals have very strong or dominant control over a particular market or industry. In fact, Islam allows monopoly if there is no effort or excessive profit is taken. However, in fact, if we investigate further, trade monopolies give rise to unhealthy competition, encourage the practice of usury, and injustice in economic distribution. One of the things that is becoming a hot topic of discussion in Indonesia this time is the practice of monopoly on TikTok shops. Researchers used the library method to find out the results of this research. Based on the facts that have occurred in Indonesia recently, trading in the TikTok shop business is detrimental to MSMEs in Indonesia because there is a trade monopoly using algorithmic gaming methods on TikTok. In Ibn Taymiyah's view, if a trade monopoly results in injustice or harms society, this may be considered an action that is contrary to Islamic principles. He emphasized the need to maintain justice in the economy and avoid oppression in trade.